Improving the understanding of the complex phase behaviour of mixtures containing various organics and supercritical carbon dioxide - Du Plessis, Susanna Hendrina (Stellenbosch : Stellenbosch University, 2025)
Du Plessis, S. H. 2025. Improving the understanding of the complex phase behaviour of mixtures containing various organics and supercritical carbon dioxide. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/a32aac46-3928-4831-9b55-e8c9365e92be